Hepatitis-Free Interval After Clotting Factor Therapy in First Infused Haemophiliacs - Morfini, M; Rafanelli, D; Longo, G; Messori, A; Rossi Ferrini, P (Thrombosis and Haemostasis, 1986)
Post-infusion hepatitis is known to occur very frequently in haemophiliacs after treatment with unheated commercial clotting factor concentrates, obtained from large plasma donation pool. On the contrary, single-donor cryoprecipitate is likely to carry a lower risk of transmitting hepatitis.To evaluate this hypothesis, we retrospectively reviewed the medical records of 25 first infused haemophiliacs (from 1981 to 1984) treated with unheated commercial clotting factor concentrates (n = 19) or cryoprecipitate (n = 6).The hepatitis-free interval after the beginning of therapy was expressed as exposure days. The end point of each patient, i.e. the hepatitis occurrence, was defined as an increase of aminotransferases (ALT and AST) and/or the seroconversion of HBV-markers, which were checked every three months.The life-table method and log-rank test showed that cryo-precipitates had a significantly longer hepatitis-free interval (p = 0.0131, log-rank test) and a lower risk of transmitting hepatitis (p = 0.01-0.05, life-table method) than the commercial concentrates. However, the safety of cryoprecipitate therapy was shown to cover only a few exposure days, and so the real advantage of this product depends on the bleeding frequency of the patient concerned.We believe that these methods and our findings may be useful to assess and compare the safety of the new “heat-treated” clotting factor concentrates.
Keywords: Post-infusion hepatitis; Clotting factor concentrates; Logrank test